STIC3: silicon photomultiplier timing chip with picosecond resolution - Stankova, Vera; Shen, Wei; Briggl, Konrad; Chen, Huangshan; Fischer, Peter; Gil, Alejandro; Harion, Tobias; Kiworra, Volker; Munwes, Yonathan; Ritzert, Michael; Schultz-Coulon, Hans-Christian (Nuclear instruments & methods in physics research. Section A, Accelerators, spectrometers, detectors and associated equipment, 2014)
The diagnostic of pancreas and prostate cancer is a challenging task due to the background noise coming from the closer organs. The EndoToFPET-US project aims to combine the synergy between metabolic and anatomical (ultrasound) image in order to improve the precision in the tumor localization. The goal of the project is to develop a Positron Emission Tomography (PET) system that provides a time-of-flight resolution of 200 ps FWHM for improving the signal to noise ratio and further to improve the medical image quality. In order to achieve this purpose an ASIC has been designed for very high timing resolution in time-of-flight (ToF) applications. In this paper we present the ASIC performance and the first characterization measurements with the 64-channels prototype version (STiC3). Measurements are performed with LYSO scintillator crystal and a Multi Pixel Photon Counter (MPPC). Measurements with the chip show an analog-front-end stage jitter of 35 ps for the first photo-electron equivalent charge and reach 18 ps for the third photo-electron. Coincidence time resolution (CTR) of 240 ps FWHM is measured with 3.1×3.1×15 mm3 LYSO crystal and pixel pitch MPPC. Further optimization including the Time-to-Digital Converter (TDC) non-linearity corrections and setup fine tuning are ongoing for achieving the desired CTR of 200 ps FWHM.
Gesehen am 06.03.2018